Penguatan Literasi Keuangan Syariah sebagai Strategi Preventif terhadap Jeratan Judi Online dan Pinjaman Online di Kalangan Remaja - M Bastomi Fahri Zusak; Ariza Fuadi; Akhmad Syakir Kurnia; FX Sugiyanto (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
This community service program aims to improve Islamic financial literacy as a preventative measure against the trap of online gambling and online loans among teenagers. The background to this activity is based on the increasing digital access that is not matched by adequate financial understanding, thus creating vulnerability to risky financial practices. The implementation method uses a participatory approach through education, training, case simulations, and mentoring. This program also integrates Islamic financial principles as an alternative, fairer and more ethical financial system. The expected results are increased financial literacy among teenagers, changes in wiser financial behavior, and a reduced potential for involvement in online gambling and illegal online loans. This program is expected to become a model of Islamic value-based financial education that can be replicated in various youth communities.